Augmented reality courseware for english vocabulary pronunciation using phonic reading technique / Juliana Jumi - Jumi, Juliana (2020)
Educational technology has rapidly grown faster due to cycles of time. Ideally, educational technology should be interactive and attractive for 4 to 6 years old preschool children learning, but some at preschool teachers still used the traditional methods in teaching. The objective of this project is to design and develop a phonic reading technique courseware by integrating Augmented Reality (AR) technology. The ADDIE model has been used as the methodology for this project, which comprises five phases. The test result shows that user agreed with the idea and accepted the courseware as learning and teaching tools. The results show that the courseware is easy to learn and easy to memorize, as it applies of phonic reading technique. In future studies, the content of the courseware is based on preschool syllabus.